2002
DOI: 10.12968/denu.2002.29.6.273
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis and Oral Care

Abstract: Multiple sclerosis is a complex neurological condition affecting sensory and motor nerve transmission. Its progression and symptoms are unpredictable and vary from person to person as well as over time. Common early symptoms include visual disturbances, facial pain or trigeminal neuralgia and paraesthesia or numbness of feet, legs, hands and arms. These, plus symptoms of spasticity, spasms, tremor, fatigue, depression and progressive disability, impact on the individual's ability to maintain oral health, cope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…As noted earlier, there are strong a priori theoretical reasons for predicting that people with multiple sclerosis will be particularly susceptible to a wide range of oral health problems, and in addition to there being moderate evidence for a link between multiple sclerosis and temporomandibular disorders, there was also suggestive evidence for an higher risk of periodontal disease and poorer oral hygiene. Poorer oral hygiene makes sense in light of the fact that motor abnormalities are a common symptom of multiple sclerosis, and performing effective oral care become more challenging with reduced muscular power/manual dexterity; fatigue and mobility limitations also make it more difficult to access routine oral care . In addition, greater periodontal disease was predicted based on the fact that like multiple sclerosis, periodontitis has an inflammatory origin .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As noted earlier, there are strong a priori theoretical reasons for predicting that people with multiple sclerosis will be particularly susceptible to a wide range of oral health problems, and in addition to there being moderate evidence for a link between multiple sclerosis and temporomandibular disorders, there was also suggestive evidence for an higher risk of periodontal disease and poorer oral hygiene. Poorer oral hygiene makes sense in light of the fact that motor abnormalities are a common symptom of multiple sclerosis, and performing effective oral care become more challenging with reduced muscular power/manual dexterity; fatigue and mobility limitations also make it more difficult to access routine oral care . In addition, greater periodontal disease was predicted based on the fact that like multiple sclerosis, periodontitis has an inflammatory origin .…”
Section: Discussionmentioning
confidence: 99%
“…This is because, firstly, performing effective oral care becomes more challenging with reduced muscular power/manual dexterity, and motor abnormalities are a common symptom of multiple sclerosis. It has also been reported that people with multiple sclerosis find it difficult to access routine oral care due to fatigue and mobility limitations, with implications for dental health care access and treatment . In addition, multiple sclerosis and periodontal disease both have an inflammatory origin, and consequently, there may be a link between these two disorders .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral and facial manifestation in MS patients, are significant for dentists especially trigeminal neuralgia (TN), trigeminal sensory neuropathy (TSN) and facial palsy (FP) [1]. As the prevalence of oral and facial manifestation in MS is high, the probability of MS can be raised, and thus preclude unnecessary treatment of these manifestations instead of the primary etiology [3].…”
Section: Introductionmentioning
confidence: 99%
“…There is currently no medical nor rehabilitative action effective against MS [7,8,9]. Patients should clearly understand that they have to live with certain limitations, and they must adapt physically and psychologically to such limitations [10].…”
Section: Introductionmentioning
confidence: 99%